MERANCANG SISTEM INFORMASI INVENTORY MENGGUNAKAN METODE WATERFALL DI PT. NUBOS PERKASA JAYA - Fauzan, Al fana; Wijaya, Setiawan Ardi; Putri, Jossie Mutiarani; Bukhari, Ahmad (LPPM Universitas Putera Batam, 2024)
This research aims to design and implement an inventory information system using the Waterfall method at PT Nubos Jaya Perkasa, a heavy equipment sales company. This system replaces the manual process in managing stock and transactions. The development stages include requirements analysis, system design (use case diagram, activity diagram, sequence diagram, class diagram, flow chart, and wireframe), and implementation with HTML, CSS, JavaScript, and XAMPP for the database. System testing using the Black-Box Testing method ensures all functions run according to specifications. The test results show that the system can add, edit, delete product data, record transactions, and monitor stock accurately. The system also provides report features to monitor operational activities. The conclusion of this research is that the web-based inventory information system at PT Nubos Jaya Perkasa improves the efficiency and accuracy of stock and transaction management, and provides real-time data for decision making. The system helps the company automate manual workflows and identify areas that can be optimized to improve productivity and customer service.